Global Impact and Challenges of Unconventional Monetary Policies. (Policy Papers; Policy Paper ;, 2013)
This paper takes stock of unconventional monetary policies (UMP) and their impact so far, and looks ahead towards exit and prospects for policy coordination. It synthesizes earlier staff work on UMP,1 the findings of a substantial and growing academic and central banking literature, as well as further staff analysis contained in the Background Paper. While some widely accepted conclusions have emerged from the large and growing number of studies on UMP, many important questions remain unsettled, as enough time has not elapsed to draw definitive conclusions. In those cases, the paper will pose the relevant questions and provide possible nswers, while recognizing the uncertainty that remains.